John Wesley's Mission of Spreading Scriptural Holiness: A Case Study in World Mission and Evangelism - Wood, Laurence W. (The Asbury journal, 2018)
A manual of discipline, called The Large Minutes, was given to all Methodist preachers when they joined John Wesley’s annual conference, containing this explanation: “God’s design in raising up the people called ‘Methodists’” was “to spread scriptural holiness over the land.” This paper will trace a narrow slice of the larger developing story of how John Wesley arrived at his distinction between justifying faith and full sanctifying grace. It will also serve as a case study to show that the call to justification by faith and a subsequent experience of sanctification by faith became the theme of his evangelistic preaching. This paper will conclude with some observations about the importance of Wesley’s holiness message for the founding of Asbury Theological Seminary and the E. Stanley Jones School of World Mission and Evangelism.